PASSIVE AND IONTOPHORETIC PERMEATION OF CAPTOPRIL GEL: AN IN VITRO AND IN VIVO STUDY - Perpustakaan UGM, i-lib ([Yogyakarta] : Universitas Gadjah Mada, 2012)
The Objective of this work was to formulate and evaluate captopril gel to assess its suitability for transdermal delivery by passive and iontophoresis. A polymer gel was prepared using hydroxypropyl methyl cellulose and in vitro skin permeability was assessed in full thickness skin of rabbits and pigs. For in vivo studies New Zealand rabbits were used. In vitro passive permeation was carried out in Franz diffusion cell but for iontophoresis, diffusion cell was modified according to Glikfield design. Iontophoresis was performed at a current density of 0.5 mA/cm² via silver /silver chloride electrodes with passive controls but for in vivo study current density was reduced to 0.1 mA/cm². Blood samples were analyzed for drug content by HPLC. Results of the in vitro study indicated that iontophoresis considerably increased the permeation rate of captopril compared to passive controls in both the skin types (P